(Invited) Overcoming Catalytic Material Challenges for Advanced Water Splitting Technologies. (3rd May 2017) - Peterson, David; Miller, Eric L.; Randolph, Katie; Vickers, James
Abstract : The emergence of hydrogen and fuel cell technologies offers the world important and potentially transformative environmental and energy security benefits. In recent years, research sponsored by the US Department of Energy's (DOE) Fuel Cell Technologies Office (FCTO) has made significant contributions to the development of these technologies. With fuel cell electric vehicles beginning to be introduced to the market, enabling technologies for the widespread production of affordable hydrogen are becoming increasingly important. One of the more versatile hydrogen production pathways is based on splitting water via either electrolytic, photoelectrochemical, or thermochemical routes. For these advanced water splitting (AWS) technologies, there are tradeoffs amongst efficiency, durability, and cost at the materials, device, and system levels that need to be balanced for low cost hydrogen production. Recent advances have been made in catalytic materials for AWS to improve these attributes; however, further developments, from new materials to scale-up of state-of-the-art (SOA) materials, are required to reach large scale technoeconomic viability. Research innovations to advance the SOA in AWS materials are being facilitated by the DOE "HydroGEN" Energy Materials Network (EMN) consortium. An overview of FCTO's Hydrogen Production Program activities with a focus on catalysts for advanced water splitting technologies and the HydroGEN consortium will be provided.